Doctors, Patients, and Interpreters' Views on the Co-Construction of Empathic Communication in Interpreter-Mediated Consultations: A Qualitative Content Analysis of Video Stimulated Recall Interviews. (October 2022) - Theys, Laura; Wermuth, Cornelia; Hsieh, Elaine; Krystallidou, Demi; Pype, Peter; Salaets, Heidi
Doctors and patients rely on verbal and nonverbal resources to co-construct clinical empathy. In language-discordant consultations, interpreters' communicative actions might compromise this process. We aim to explore doctors, patients, and professional interpreters' perspectives on their own and others' actions during their empathic interaction in interpreter-mediated consultations (IMCs). We analyzed 20 video stimulated recall interviews with doctors, patients, and interpreters using qualitative content analysis. Doctors and patients found ways to connect with each other on the level of empathic communication (EC) that is not limited by interpreters' alterations or disengaged demeanor. Some aspects of doctors and interpreters' professional practices might jeopardize the co-construction of EC in IMCs. The co-construction of EC in IMCs is not only subject to participants' communicative (inter)actions, but also to organizational and subjective factors. These results provide evidence of the transactional process between the behavioral, cognitive, and affective components of clinical empathy in the context of IMCs.